The Influence of Lifestyle, Peers, and Self-Control on the Effectiveness of Students' Personal Financial Management at Muhammadiyah University of Palu - Siti Ainafizah Eka Putri; Rajindra; Rasmi Nur Anggraeni; Nur Rizkianti (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to determine the effect of lifestyle, peer influence, and self-control on the effectiveness of personal financial management among students at Universitas Muhammadiyah Palu. The analytical method used in this study is multiple linear regression analysis with a sample size of (fill in according to your data) respondents. The results of the regression analysis show the following equation:Y = 10.364 + 0.355X₁ + 0.393X₂ + 0.243X₃.The regression coefficient for the lifestyle variable (X₁) of 0.355 indicates that lifestyle has a positive effect on the effectiveness of students’ personal financial management. The peer variable (X₂) also has a positive effect on the effectiveness of personal financial management. This means that a supportive peer environment encourages students to manage their finances more effectively. The regression coefficient for the self-control variable (X₃) of 0.243 indicates that self-control has a positive effect on the effectiveness of personal financial management. Thus, the hypothesis stating that lifestyle, peer influence, and self-control have a positive effect on the effectiveness of personal financial management among students at Universitas Muhammadiyah Palu is accepted.